Demand for Narcotics in Thailand, with Policy Implications - Sukharomana, Renu; Chang, Chia-Lin (Journal of Reviews on Global Economics, 2017)
The paper examines the demand for narcotic drugs, based on Becker (1968), as purported rational behavior of human beings. The results from sampling surveys in eight provinces in Thailand in 2014, representing nationwide drug users/addicts, show that the demand for narcotics (amphetamines, ice drug, and marijuana) are price inelastic (between -0.533 and -0.701), as well as normal goods. The key econometric coefficients in models A and B are 0.192 and 0.0467, respectively, and an increase in income will lead to an increase in the demand for narcotics. In addition, factors affecting the demand for narcotics are the age and age squared of the user, friendship, family member relationship, social relationship, reasons for drug use, risk behavior, and expected punishment. Public policy implications are also proposed and analysed.